Critical factors influencing bid mark-up decision in public street project: a review / Huzairi Zainul Azlan, Shamsida Saidan Khaderi and Anis Sazira Bakri - Zainul Azlan, Huzairi; Khaderi, Shamsida Saidan; Bakri, Anis Sazira (UiTM Press, 2024)
Deciding a bid price with an appropriate mark-up added to the estimated project cost is essential for the contractors' business survival. However, the competitive environment had influenced contractors to offer the lowest bid price, leading to the submission of unrealistically low prices to win bids. This practice can impact disputes and adversarial relationships between parties during construction and provide an additional risk to the project delay, cost overrun, quality compromise and failure to complete the project. Therefore, this paper aims to provide an overview of the literature on critical factors influencing bid mark-up decisions in public street projects. The objectives are to identify methods and tools, including the critical factors in determining the contractors' bid mark-up decision. The approach is based on analysing pertinent publications on the theme. The top five (5) ranked factors influencing contractors' decision on bid mark-up size can be found in the literature: the number of bidders, the competitiveness of other bidders, relationship and experience with clients, experience on similar projects and project size. Besides that, the determination of mark-up size is based on experience, intuition, past bidding results, past bidding patterns of competitors, the client's tender estimate, the client's record, and financial ability.